2018
DOI: 10.1002/cne.24502
|View full text |Cite
|
Sign up to set email alerts
|

Input–output organization of the mouse claustrum

Abstract: Progress in determining the precise organization and function of the claustrum has been hindered by the difficulty in reliably targeting these neurons. To overcome this, we used a projection-based targeting strategy to selectively label claustrum principal neurons. Combined with adeno-associated virus (AAV) and monosynaptic rabies tracing techniques, we systematically examined the pre-synaptic input and axonal output of this structure. We found that claustrum neurons projecting to retrosplenial cortex (RSP) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
218
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(246 citation statements)
references
References 56 publications
(133 reference statements)
26
218
2
Order By: Relevance
“…Moreover, analysis of DiI labeling of cingulate cortex projection neurons revealed DiI‐positive fibers in close vicinity to GFP pos EPP neurons. Strong connectivity between the cingulate cortex and the claustrum–endopiriform complex was reported previously (Behan & Haberly, ; Condé et al, ; Qadir et al, ; Smith et al, ; Wang et al, ; Watson et al, ; White et al, ; Zingg et al, ), confirming our observations that these GFP pos neurons are located within the endopiriform nucleus. The endopiriform nucleus is strongly connected to the amygdaloid complex, therefore retrograde labeling of amygdalar projection neurons could further corroborate our finding that GFP pos neurons are located within the endopiriform nucleus (Majak et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, analysis of DiI labeling of cingulate cortex projection neurons revealed DiI‐positive fibers in close vicinity to GFP pos EPP neurons. Strong connectivity between the cingulate cortex and the claustrum–endopiriform complex was reported previously (Behan & Haberly, ; Condé et al, ; Qadir et al, ; Smith et al, ; Wang et al, ; Watson et al, ; White et al, ; Zingg et al, ), confirming our observations that these GFP pos neurons are located within the endopiriform nucleus. The endopiriform nucleus is strongly connected to the amygdaloid complex, therefore retrograde labeling of amygdalar projection neurons could further corroborate our finding that GFP pos neurons are located within the endopiriform nucleus (Majak et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with previous reports on PV expression in the nucleus endopiriformis (Real, Dávila, & Guirado, 2003;Wang et al, 2017), we only found scarce immunoreactivity to PV in the region with the highest density of GFP pos neurons (Figure 1b). Furthermore, previous studies reported on a strong connectivity between the claustrumendopiriform complex and the anterior cingulate and infralimbic cortex (Behan & Haberly, 1999;Condé, Maire-Lepoivre, Audinat, & Crépel, 1995;Qadir et al, 2018;Smith et al, 2018;Wang et al, 2017;White et al, 2017;Zingg, Dong, Tao, & Zhang, 2018). Therefore, we injected a DiI crystal into the anterior cingulate cortex and determined the presence of DiI-positive fibers in the area with the highest density of GFP pos neurons (Supporting Information Figure S2).…”
Section: Gfp Pos Cells Are Located In the Endopiriform Nucleusmentioning
confidence: 99%
“…However, it remains largely unknown how population-level projection patterns are reflected at the single neuron level. Triple retrograde tracing studies suggest that individual neurons within a brain region often have heterogeneous axonal projection patterns [19][20][21] . Thus, characterizing single neuron axonal projections through reconstruction of complete morphologies not only provides critical information related to classifying cell types, but also how neural signals are organized and transmitted to their target regions.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the cellular composition, form, connectivity, and function of the claustrum represents a major challenge and here is where neuroinformatics can make an enormous contribution. With advances in the examination of brain connectivity in human 25 and in non-humans 26 and the availability of novel mathematical frameworks for analysis, 27 perhaps the next few years will see fuller computational and conceptual innovations for claustral characterization. 28 These may, finally, reveal a satisfying description of the claustrum and its role in cognition, conscious attention, and in clinical syndromes.…”
mentioning
confidence: 99%